Pakistan : Third Review Under the Stand-By Arrangement and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2001)
Pakistan showed commendable performance under the Stand-By Arrangement. Executive Directors noted the substantial progress in the structural reforms, but expressed concerns about the slippage in revenue performance, and heavy foreign exchange intervention in the kerb market to meet the reserves' program targets. They stressed the need to build foreign exchange reserves, improve monetary and exchange rates, liberalize the foreign exchange interbank market, improve governance, and strengthen the financial system. They agreed that Pakistan has successfully completed the third review under the Stand-By Arrangement, and approved a waiver.